2002
DOI: 10.1177/153244000200200103
|View full text |Cite
|
Sign up to set email alerts
|

Explaining State Internet Sales Taxation: New Economy, Old-Fashioned Interest Group Politics

Abstract: Retail sales on the Internet are growing at a rapid pace. Some states have tapped into this potential revenue source with Internet sales taxes, while others have not. What are the factors that lead states to make these policy decisions? Using a 50-state comparative research design, we find that interest groups, as much as the partisan and economic factors emphasized in previous research on state tax policy, are correlated with adoptions of these state tax innovations. Furthermore, this interest group influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Tax increases are extremely unpopular, making incremental adjustments in existing tax rates difficult, if not impossible, to implement during even the best fiscal circumstances. Thus, although a few states raised cigarette and other excise taxes during the latest economic downturn, most showed a greater inclination toward taxing previously untapped revenue sources (such as the Internet) while relying primarily on short-term budgetary fixes (Best and Teske 2002). This general reluctance to increase taxes to raise additional revenue contrasts with the pattern of Medicaid cost containment in my dataset, in which states frequently relied on incremental changes in provider payments (Smith et al 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Tax increases are extremely unpopular, making incremental adjustments in existing tax rates difficult, if not impossible, to implement during even the best fiscal circumstances. Thus, although a few states raised cigarette and other excise taxes during the latest economic downturn, most showed a greater inclination toward taxing previously untapped revenue sources (such as the Internet) while relying primarily on short-term budgetary fixes (Best and Teske 2002). This general reluctance to increase taxes to raise additional revenue contrasts with the pattern of Medicaid cost containment in my dataset, in which states frequently relied on incremental changes in provider payments (Smith et al 2004).…”
Section: Discussionmentioning
confidence: 83%
“…Most research in the political science tradition, however, has focused on innovation and diffusion in the American states. Particular policy areas examined include lotteries (Berry and Berry 1990;Filer, Maok, and Uze 1988), state administration (Berry 1994a), tax policy (Berry and Berry 1992;Best and Teske 2002), constitutional provisions (Benjamin 1985), hate crime legislation (Grattet, Jenness, and Curry 1998;Haider-Markel 1998), welfare policy (Gray 1973a), education policy (Mintrom 1997a;1997b;Mintrom and Vergari 1998), social services (Sigelman and Smith 1981), marriage (Haider-Markel 2001), environmental policy (Blomquist 1991;Rosenbaum 1976), tort law (Canon and Baum 1981;Lutz 1997), tobacco lawsuits (Winder and LaPlant 2000), insurance regulation (Cheit 1993;Lambert and McGuire 1990), energy policy (Andrews 2000;Freeman 1985), judicial administration (Glick 1981;Puro, Bergerson, and Puro 1985), living wills (Glick and Hays 1991;Hays and Glick 1997), crime policy (Hays 1996), health policy (Satterthwaite 2002), licensing laws (Lutz 1986), abortion policy (Mooney and Lee 1995;Arceneaux 2002), ethics policy (Rosenson 2003), juvenile corrections , and others. Rather than focusing on individual policies, still other researchers describe innovation and diffusion across multiple policy areas…”
Section: Diffusion and Innovation Studies: Explaining Variation In Discrete Policy Adoptionsmentioning
confidence: 99%
“…Overall, the results do not show statistical relationships between factors that are perceived to be associated with taxing Internet sales. Best and Teske (2002) examine the impact of interest groups and political and economic factors and found that they were correlated with…”
Section: A Government's Perspectivementioning
confidence: 98%